Fallibility at Work Rethinking Excellence and Error in Organizations - Kvalnes, Øyvind (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is published open access under a CC BY 4.0 license.  ‘This is an exciting, groundbreaking book. With an astonishing array of examples and a brilliant eye for the essential, Øyvind Kvalnes takes the Socratic motto of knowing yourself to our everyday lives in the workplace. Applied philosophy at its best, the book will affect the way you do your work and live your life.’ —Professor Esa Saarinen, Aalto University This book addresses how organizations can deal with human fallibility in order to create space for excellence at work. Some mistakes in work settings put lives at risk, while others create openings for innovative breakthroughs. In order to deal constructively with fallibility, an organization needs a communication climate where it is normal to voice opinions, admit mistakes, and ask for help in critical situations. The book builds on interviews with practitioners in healthcare, aviation, IT, public governance, and industry. It connects narratives from these fields with theories from organizational psychology and philosophy, as well as from positive organizational scholarship. In the final chapter, an overall ethics of fallibility at work is outlined. Fallibility at Work contributes to research in multiple academic disciplines, but also reaches out to practitioners who are interested in the connections between error and excellence in organizations.